Fluorofluorescent Perylene Bisimides - Yoshinaga, Kosuke; Swager, Timothy M. (Synlett, 2018)
Perfluorinated liquids can exhibit immiscibility with organic solvents and water, and provide orthogonal opportunities in chemistry. Examples of emissive dyes that display only fluorous phase solubility are limited, despite the many potential applications. Perylene bisimides are among the most versatile dyes and are known for their outstanding stability and high quantum yields. Herein, we report the synthesis of two new “fluorofluorescent” perylene bisimide dyes, designed to be soluble in the fluorous phases. These two dyes possess unique photophysical properties, including dramatic increases in fluorescence quantum yields when treated with Brønsted acids as well as aggregation in the fluorous phase.
Keywords: perylene bisimides; fluorines; Heck reaction; fluorescence; aggregation